ATTITUDE OF CUSTOMERS TOWARDS E-BANKING SERVICES OFFERED BY PUBLIC AND PRIVATE SECTOR BANKS IN TIRUNELVELI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
With the rapid advancement of technology and increasing internet penetration, e-banking has become a vital component of the banking sector, offering numerous benefits such as convenience, speed, and cost efficiency. The research employs a quantitative approach, surveying a diverse sample of bank customers to gauge their perceptions, satisfaction levels, and the factors influencing their adoption of e-banking services. Key findings indicate a positive overall attitude towards e-banking, with significant differences in customer satisfaction and usage patterns between public and private sector banks. Public sector bank customers cited reliability and trust as primary factors for their preference, whereas private sector bank customers were more influenced by advanced technological features and user-friendly interfaces. The study highlights the need for banks to address specific customer concerns and enhance the user experience to foster greater acceptance and utilization of e-banking services. These insights are crucial for banks aiming to improve their digital offerings and achieve competitive advantage in the evolving financial landscape.